China on Preserving Energy Resilience: An Analysis of China’s Carbon Market System - Dewanto, Maurichio; Awuy, Jennye Maria Paule (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2024)
The urgency of energy transition continuously presents itself in various conditions and situations. Within this article, the background used to visualize the problem is of how the energy transition could be achieved whilst still preserving energy resilience. The way to do so is through the implementation of an accurate and effective carbon market system. China, as one of the biggest contributors of energy and carbon emissions, has the urgency to implement said system. This article tries to analyze using the method of qualitative research through the carbon market effectivity—particularly within China's Carbon Market System—that is purposefully one of the most significant efforts to urge energy transition, the issues that are disruptive and harmful towards the projection of results are analyzed. This article seeks to find the core problem and reasonings behind the ineffectiveness of China’s carbon market. Keywords: Energy transition, energy resilience, carbon market, China, foreign affairs